Preparation method of nanometer enhanced 3D printing metal powder material

Through the detailed design and parameter optimization of the preparation method of nano-reinforced 3D printing metal powder material, the problems of uneven dispersion of nanoparticles and complex preparation processes are solved, and the material performance improvement and process simplification are achieved, which is suitable for large-scale production.

CN119501051APending Publication Date: 2025-02-25XIANXIAN JIANTOU TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411640778.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the existing nano-reinforced 3D printed metal powder material preparation methods, the dispersion of nanoparticles in the metal matrix is ​​uneven and prone to agglomeration, resulting in poor improvement in material performance and unstable improvement, and the preparation process is complex, difficult to control parameters, high cost and is not conducive to large-scale production.

Method used

Through detailed design and parameter optimization, each step, including raw material preparation, surface treatment, mixing process, ball milling treatment, and drying and screening, the uniform dispersion of nanoparticles in the metal matrix is ​​achieved, the preparation process is simplified, and the production cost is reduced.

Benefits of technology

The uniform dispersion of nanoparticles in the metal matrix is ​​achieved, which significantly improves the comprehensive performance of the material, such as strength, hardness, wear resistance, etc. At the same time, the process is simplified, the production cost is reduced, and it is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of a nano-enhanced 3D printing metal powder material, and belongs to the technical field of 3D printing materials.The preparation method of the nano-enhanced 3D printing metal powder material comprises the steps that metal matrix powder such as stainless steel, aluminum alloy or titanium alloy with the size of 10-50 microns and nano-enhanced particles such as carbon nanotubes with the size of 10-50 nm are selected; the metal matrix powder is subjected to heat preservation for 2-4 hours at the temperature of 300-500 DEG C, the nano reinforced particles are subjected to ultrasonic dispersion for 30-60 minutes by using a 1%-3% surfactant solution, the metal matrix powder and the nano reinforced particles are mixed according to the proportion of 0.5%-3%, the mixture is stirred for 2-4 hours at the speed of 1000-2000 revolutions per minute and then subjected to ball milling, the speed of 300-500 revolutions per minute and the speed of 8-12 hours are adjusted according to the ball-to-material ratio of 5: 1-10: 1, finally, the powder is dried for 4-8 hours at the temperature of 80-120 DEG C, 10-50 [mu] m powder is screened, and the nano reinforced particles are obtained. The method solves the problems of uneven dispersion of nanoparticles, complex process and the like, improves the comprehensive performance of the material, can meet the 3D printing requirements in different fields, and promotes the application and development of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of 3D printing materials, and in particular relates to a method for preparing nano-enhanced 3D printing metal powder materials. Background Art

[0002] With the continuous development of 3D printing technology, its application in various fields is becoming more and more extensive, and the performance requirements for 3D printed metal powder materials are also getting higher and higher. Traditional 3D printed metal powder materials have limitations in certain performance aspects. For example, strength, hardness, wear resistance, etc. cannot meet the needs of some high-end applications. In order to improve these properties, introducing nanomaterials into metal powders has become a research direction. However, there are many problems with the existing preparation methods of nano-enhanced 3D printed metal powder materials. On the one hand, the dispersion uniformity of nanoparticles in the metal matrix is ​​difficult to ensure, and agglomeration is prone to occur, which leads to poor and unstable material performance improvement effects. On the other hand, the preparation process is often more complicated, involving multiple links and parameters that are difficult to control, which increases production costs and production difficulties, and is not conducive to large-scale production.

[0003] The present invention aims to provide a method for preparing nano-enhanced 3D printing metal powder materials to solve the problems existing in the above-mentioned prior art. By carrying out detailed design and parameter optimization of various steps such as raw material preparation, surface treatment, mixing process, ball milling treatment, drying and screening, the uniform dispersion of nanoparticles in the metal matrix is ​​achieved, agglomeration is avoided, and the comprehensive performance of the material is improved. At the same time, the preparation process is simplified to make it easier to operate and control, reduce production costs, and improve production efficiency, thereby meeting the high performance requirements of 3D printing metal powder materials in different fields and promoting the application and development of 3D printing technology in more fields. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing nano-enhanced 3D printing metal powder materials, aiming to solve the problems in the prior art that nanoparticles are unevenly dispersed and easily agglomerated in the metal matrix, resulting in poor and unstable material performance improvement, as well as complex preparation process, difficult to control parameters, high cost and not conducive to large-scale production.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a nano-enhanced 3D printing metal powder material, characterized in that it comprises the following steps:

[0007] Step 1: Raw material preparation: Select metal matrix powder, which is one of stainless steel powder, aluminum alloy powder or titanium alloy powder, and the powder particle size range is 10-50 μm;

[0008] Prepare nano-reinforced particles, which are one of nano-carbon tubes, nano-ceramic particles (such as aluminum oxide, zirconium oxide, etc.) or nano-metal particles (such as nickel, cobalt, etc.), and the particle size of the nano-particles ranges from 10 to 50 nm.

[0009] Step 2: Surface treatment: Place the metal matrix powder in a vacuum heating furnace and keep it at 300-500°C for 2-4 hours;

[0010] The nano-enhanced particles are placed in a solution containing a surfactant for ultrasonic dispersion treatment, wherein the mass fraction of the surfactant is 1%-3%, and the ultrasonic treatment time is 30-60 minutes.

[0011] Step 3: Mixing process: Add the surface treated metal matrix powder and nano-enhanced particle solution into a high-speed stirrer at a ratio of 0.5% to 3% of the mass of the nano-enhanced particles to the metal matrix powder, and stir at a speed of 1000 to 2000 rpm for 2 to 4 hours.

[0012] Step 4: ball milling: put the mixed powder into a ball mill for ball milling. The speed of the ball mill is 300-500 rpm. The ball milling time is 8-12 hours. Stainless steel balls are used as grinding balls. The ball-to-material ratio is 5:1-10:1.

[0013] Step 5: Drying and sieving: The ball-milled powder is dried in a vacuum drying oven at a drying temperature of 80-120°C for 4-8 hours;

[0014] The dried powder was sieved using a vibrating screen, and powder with a particle size range of 10-50 μm was selected as nano-enhanced 3D printing metal powder material.

[0015] As a preferred solution of the present invention, in step one, the particle size of the stainless steel powder is preferably 20-30 μm, the particle size of the aluminum alloy powder is preferably 30-40 μm, and the particle size of the titanium alloy powder is preferably 15-45 μm.

[0016] As a preferred solution of the present invention, in step 1, the diameter of the carbon nanotube is 20-30 nm and the length is 10-20 μm; the particle size of the nano ceramic particles is preferably 30-40 nm; and the particle size of the nano metal particles is preferably 20-30 nm.

[0017] As a preferred scheme of the present invention, in step 2, when the metal matrix powder is stainless steel powder, the insulation temperature of the vacuum heating furnace is preferably 400°C, and the insulation time is 3 hours; when the metal matrix powder is aluminum alloy powder, the insulation temperature is preferably 350°C, and the insulation time is 2.5 hours; when the metal matrix powder is titanium alloy powder, the insulation temperature is preferably 450°C, and the insulation time is 3.5 hours.

[0018] As a preferred solution of the present invention, in step 2, during the ultrasonic dispersion treatment, if the nano-reinforced particles are nano-carbon tubes, the mass fraction of the surfactant is preferably 2%, and the ultrasonic treatment time is 45 minutes; if the nano-reinforced particles are nano-ceramic particles, the mass fraction of the surfactant is preferably 1.5%, and the ultrasonic treatment time is 50 minutes; if the nano-reinforced particles are nano-metal particles, the mass fraction of the surfactant is preferably 2.5%, and the ultrasonic treatment time is 35 minutes.

[0019] As a preferred scheme of the present invention, in step three, when the nano-reinforced particles are nano-carbon tube-reinforced stainless steel powder, the proportion of nano-carbon tubes to the mass of the stainless steel powder is preferably 1%, the stirring speed is 1500 rpm, and the stirring time is 3 hours; when the nano-reinforced particles are nano-alumina-reinforced aluminum alloy powder, the proportion of nano-alumina to the mass of the aluminum alloy powder is preferably 2%, the stirring speed is 1800 rpm, and the stirring time is 2.5 hours; when the nano-reinforced particles are nano-nickel-reinforced titanium alloy powder, the proportion of nano-nickel to the mass of the titanium alloy powder is preferably 1.5%, the stirring speed is 1600 rpm, and the stirring time is 3.5 hours.

[0020] As a preferred scheme of the present invention, in step four, when ball milling a mixed powder of stainless steel powder and nano-reinforced particles, the ball mill speed is preferably 400 rpm, the ball milling time is 10 hours, and the ball-to-material ratio is 8:1; when ball milling a mixed powder of aluminum alloy powder and nano-reinforced particles, the ball mill speed is preferably 350 rpm, the ball milling time is 11 hours, and the ball-to-material ratio is 7:1; when ball milling a mixed powder of titanium alloy powder and nano-reinforced particles, the ball mill speed is preferably 450 rpm, the ball milling time is 9 hours, and the ball-to-material ratio is 9:1.

[0021] As a preferred scheme of the present invention, in step five, the drying temperature is preferably 100°C and the drying time is 6 hours; when screening stainless steel powder-based nano-enhanced materials, the powder with a particle size of 20-30μm is vibrated and screened; when screening aluminum alloy powder-based nano-enhanced materials, the powder with a particle size of 30-40μm is vibrated and screened; when screening titanium alloy powder-based nano-enhanced materials, the powder with a particle size of 15-45μm is vibrated and screened.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. In this scheme, the uniform dispersion of nanoparticles in the metal matrix is ​​achieved by detailed design and parameter optimization of each step such as raw material preparation, surface treatment, mixing process, ball milling, drying and screening. In the raw material preparation stage, the appropriate metal matrix powder particle size and nanoparticle size range are selected to lay the foundation for subsequent uniform mixing. In the surface treatment process, the metal matrix powder is preheated to remove impurities, and the nanoparticles are ultrasonically dispersed to make them uniformly dispersed in the solution. In the mixing process, the treated metal matrix powder and the nanoparticle solution are mixed under appropriate stirring conditions according to a specific ratio to further ensure that the nanoparticles are uniformly attached to the surface of the metal matrix powder. In the ball milling process, the powder particles are further refined by reasonably setting the ball mill speed, time and ball-to-material ratio, and the uniformity of the dispersion of nanoparticles in the metal matrix is ​​improved. Finally, after drying and screening, a 3D printing metal powder material with uniform particle size and uniform dispersion of nanoparticles is obtained. Such uniformly dispersed nanoparticles can give full play to their reinforcing effect and significantly improve the comprehensive properties of the material, such as strength, hardness, wear resistance, etc.

[0024] 2. In this scheme, the preparation process is simplified by optimizing the parameters and conditions of each preparation step. For example, in the surface treatment step, the optimal preheating temperature and time of different metal matrix powders and the optimal ultrasonic dispersion conditions of different nanoparticles are clarified, making the operation simpler and clearer. In the mixing process, the reasonable proportion range of nanoparticles to the mass of the metal matrix powder is determined, and the appropriate stirring speed and time are given, reducing the risk of failure due to improper parameter selection. In the ball milling and drying and screening steps, clear parameter settings are also given, making the entire preparation process easy to operate and control. The simplified preparation process reduces production costs, improves production efficiency, and is conducive to large-scale production, thereby being able to meet the high-performance requirements of 3D printing metal powder materials in different fields and promote the application and development of 3D printing technology in more fields. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] The present invention provides the following technical solutions:

[0028] A method for preparing a nano-enhanced 3D printing metal powder material, characterized in that it comprises the following steps:

[0029] Step 1: Raw material preparation: Select metal matrix powder, which is one of stainless steel powder, aluminum alloy powder or titanium alloy powder, and the powder particle size range is 10-50 μm;

[0030] Prepare nano-reinforced particles, which are one of nano-carbon tubes, nano-ceramic particles (such as aluminum oxide, zirconium oxide, etc.) or nano-metal particles (such as nickel, cobalt, etc.), and the particle size of the nano-particles ranges from 10 to 50 nm.

[0031] Step 2: Surface treatment: Place the metal matrix powder in a vacuum heating furnace and keep it at 300-500°C for 2-4 hours;

[0032] The nano-enhanced particles are placed in a solution containing a surfactant for ultrasonic dispersion treatment, wherein the mass fraction of the surfactant is 1%-3%, and the ultrasonic treatment time is 30-60 minutes.

[0033] Step 3: Mixing process: Add the surface treated metal matrix powder and nano-enhanced particle solution into a high-speed stirrer at a ratio of 0.5% to 3% of the mass of the nano-enhanced particles to the metal matrix powder, and stir at a speed of 1000 to 2000 rpm for 2 to 4 hours.

[0034] Step 4: ball milling: put the mixed powder into a ball mill for ball milling. The speed of the ball mill is 300-500 rpm. The ball milling time is 8-12 hours. Stainless steel balls are used as grinding balls. The ball-to-material ratio is 5:1-10:1.

[0035] Step 5: Drying and sieving: The ball-milled powder is dried in a vacuum drying oven at a drying temperature of 80-120°C for 4-8 hours;

[0036] The dried powder was sieved using a vibrating screen, and powder with a particle size range of 10-50 μm was selected as nano-enhanced 3D printing metal powder material.

[0037] In a specific embodiment of the present invention, step 1: raw material preparation:

[0038] (I) Selection of metal matrix powder: Diverse material types: The optional metal matrix powders include stainless steel powder, aluminum alloy powder or titanium alloy powder. This provides room for selection for the diverse demands for material properties in different application scenarios. For example, stainless steel powder has good corrosion resistance and strength, and is suitable for some fields with high requirements for structural strength and environmental resistance; aluminum alloy powder has advantages in aerospace and other fields due to its light weight and good thermal conductivity; titanium alloy powder is often used in medical equipment and other fields because of its high strength and good biocompatibility.

[0039] Particle size range limitation: The powder particle size range is clearly defined as 10-50μm. The selection of this particle size range is carefully considered, which can not only ensure the good fluidity and dispersibility of the powder in the subsequent process, but also meet the requirements of 3D printing for material molding accuracy. Smaller particle sizes help improve the sintering performance of the material, so that the printed parts have a denser structure and better mechanical properties; while a larger particle size range reduces production costs to a certain extent, while avoiding problems such as agglomeration that may be caused by overly fine powders.

[0040] (II) Selection of nano-enhanced particles: A wide variety of nano-particles: Nano-enhanced particles can be selected from nano-carbon tubes, nano-ceramic particles (such as alumina, zirconium oxide, etc.) or nano-metal particles (such as nickel, cobalt, etc.). These nanomaterials each have unique performance advantages and can bring different performance improvements to metal matrix powders. Nano-carbon tubes have excellent mechanical properties and electrical conductivity, which can improve the strength and conductivity of materials; nano-ceramic particles can enhance the hardness, wear resistance and high temperature resistance of materials; nano-metal particles can improve the toughness and conductivity of materials.

[0041] Particle size range: The particle size range of nanoparticles is 10-50nm. Nanoscale particles have a large specific surface area and surface activity, and can produce strong interface interactions with the metal matrix, thereby significantly improving the overall performance of the material. Smaller particle sizes help to better exert the nano effect, but at the same time increase the possibility of particle agglomeration, so corresponding dispersion measures need to be taken during the preparation process.

[0042] 3. Step 2: Surface treatment:

[0043] (i) Metal matrix powder treatment: Vacuum heating treatment: The metal matrix powder is placed in a vacuum heating furnace for treatment, the purpose of which is to remove adsorbed gases and moisture on the surface of the powder. Keep warm at 300-500°C for 2-4 hours. This temperature and time range setting can effectively remove impurities without significantly affecting the physical and chemical properties of the metal matrix. The vacuum environment can prevent the powder from oxidizing during the heating process, ensuring the quality of the powder and the smooth progress of subsequent processes. Different metal matrices may require slightly different treatment temperatures and times to achieve the best treatment effect. For example, for some more active metals such as aluminum alloys, relatively low temperatures and shorter times may be required to avoid excessive oxidation or other adverse reactions.

[0044] (ii) Treatment of nano-reinforced particles: ultrasonic dispersion and application of surfactants: The nano-reinforced particles are placed in a solution containing a surfactant for ultrasonic dispersion treatment. The role of the surfactant is to reduce the surface energy of the nanoparticles and increase the repulsion between the particles, so that they are evenly dispersed in the solution. A surfactant with a mass fraction of 1%-3% can effectively disperse the nanoparticles without negatively affecting the performance of the material. The ultrasonic treatment time is 30-60 minutes. The cavitation effect and mechanical stirring generated by ultrasonic vibration can further break up the agglomeration between the nanoparticles and make them evenly dispersed in the solution. This step is crucial to ensure that the nanoparticles are evenly distributed when they are subsequently mixed with the metal matrix powder, which directly affects the performance uniformity and stability of the final material.

[0045] 4. Step 3: Mixing process: Proportion control: Mix according to the ratio of 0.5%-3% of the mass of the metal matrix powder by the nano-reinforced particles. The determination of this ratio range is based on a large number of experiments and theoretical studies. It can not only give full play to the performance improvement effect of the nano-reinforced particles, but also will not cause the processing performance of the material to decrease or other adverse reactions due to excessive nano-particle content. Different combinations of nano-reinforced particles and metal matrices may need to be appropriately adjusted within this range to achieve the best performance match. For example, for some application scenarios with higher strength requirements, it may be necessary to appropriately increase the proportion of nano-reinforced particles; for situations where processing performance is important, it may need to be controlled within a lower ratio range.

[0046] High-speed stirring conditions: Stir for 2-4 hours at a speed of 1000-2000 rpm. High-speed stirring enables the nano-reinforced particles to fully contact and mix with the metal matrix powder and evenly adhere to the surface of the metal matrix powder. The selection of stirring speed and time needs to comprehensively consider factors such as mixing effect and equipment performance. Higher speeds and longer times can improve the uniformity of mixing, but may also cause problems such as powder heating and agglomeration, so reasonable optimization is required in actual operation.

[0047] 5. Step 4: Ball milling: Ball milling parameter setting: Put the mixed powder into a ball mill for ball milling. The speed of the ball mill is 300-500 rpm and the ball milling time is 8-12 hours. The ball milling process further refines the powder particles through the collision, extrusion and friction between the grinding balls and the powder, improves the dispersion uniformity of the nano-enhanced particles in the metal matrix, and promotes the interface bonding between the two. A reasonable combination of speed and time is essential to obtain a good ball milling effect. Lower speeds and longer times may be more conducive to uniform mixing and particle refinement, but will increase the production cycle; higher speeds may cause excessive wear of the powder or introduce impurities, affecting material properties. Therefore, it is necessary to optimize the selection based on the specific material system and equipment conditions.

[0048] Grinding ball selection and ball-to-material ratio: stainless steel balls are used as grinding balls, and the ball-to-material ratio is 5:1-10:1. Stainless steel balls have good wear resistance and hardness, and can maintain stable performance during the ball milling process to avoid contamination of the powder. The setting of the ball-to-material ratio affects the efficiency and effect of ball milling. The appropriate ball-to-material ratio can ensure that the powder is fully ground and mixed during the ball milling process, while avoiding excessive collisions between grinding balls and energy waste.

[0049] 6. Step 5: Drying and sieving: (i) Drying treatment: Vacuum drying conditions: The ball-milled powder is dried in a vacuum drying oven at a drying temperature of 80-120°C for 4-8 hours. Vacuum drying can effectively remove moisture from the powder to prevent oxidation or other chemical reactions during subsequent storage and use. At the same time, a lower drying temperature can prevent the powder from changing in performance or agglomerating due to overheating. The determination of the drying time needs to be adjusted according to the moisture content of the powder and the performance of the drying equipment to ensure that the powder is completely dry without affecting its performance.

[0050] (ii) Screening treatment: Particle size screening: Use a vibrating screen to screen the dried powder, and select powder with a particle size range of 10-50μm as nano-enhanced 3D printing metal powder material. The purpose of this step is to ensure the uniformity of the particle size of the final product and meet the requirements of 3D printing for material particle size. Through screening, particles that are too large or too small can be removed, improving the molding quality and printing accuracy of the material. Different application scenarios may have different requirements for the particle size range, so in actual production, appropriate adjustments can be made according to specific needs.

[0051] In summary, the described method for preparing nano-enhanced 3D printing metal powder materials realizes the whole process control from raw material selection to final product preparation through detailed regulations and parameter limitations of each step, aiming to obtain nano-enhanced 3D printing metal powder materials with excellent performance, uniformity and stability, and provides a reliable material basis for the widespread application of 3D printing technology.

[0052] Specifically in this solution, in step 1, the particle size of the stainless steel powder is preferably 20-30 μm, the particle size of the aluminum alloy powder is preferably 30-40 μm, and the particle size of the titanium alloy powder is preferably 15-45 μm.

[0053] In this embodiment: stainless steel powder with a particle size of 20-30μm is selected. The selection of this particle size range has many advantages. First, from the perspective of molding, stainless steel powder in this particle size range can be well spread and melted during the 3D printing process to form a uniform layered structure, thereby ensuring the dimensional accuracy and surface quality of the print. For example, when making parts with fine structures, smaller particle sizes help fill tiny gaps, making the surface of the print smoother and reducing the workload of subsequent processing. Secondly, from the performance point of view, the moderate particle size can make the powder fully densified during the sintering process, thereby improving the strength and hardness of the print. Compared with stainless steel powder with larger particle size, powder of 20-30μm can better combine with nano-enhanced particles, exert the effect of nano-enhancement, and improve the comprehensive performance of the material.

[0054] Select powder with a particle size of 30-40μm. Aluminum alloy has the characteristics of light weight and good thermal conductivity, and is widely used in aerospace and other fields. The selection of this particle size range takes into account both the characteristics of aluminum alloy and the process requirements of 3D printing. In the 3D printing process, 30-40μm aluminum alloy powder can achieve rapid melting and solidification while ensuring fluidity, which is beneficial to improving printing efficiency. At the same time, this particle size range also helps to maintain good thermal conductivity during the printing process and avoid deformation or defects caused by local overheating. When mixed with nano-reinforced particles, aluminum alloy powder of this particle size can better carry nanoparticles and evenly disperse the nano-reinforced phase, thereby improving the mechanical properties and wear resistance of the material, and meeting the high performance requirements of aerospace parts for materials;

[0055] The particle size of titanium alloy powder is preferably 15-45μm. Titanium alloy has important applications in medical devices and other fields due to its high strength and good biocompatibility. The particle size range of 15-45μm can take into account the formability and performance requirements of titanium alloy powder. When 3D printing medical devices, the smaller particle size can fill complex structures to ensure the accuracy and detail of the parts; while the larger particle size can provide a certain support strength to prevent the parts from deforming during the printing process. In addition, in synergy with nano-reinforced particles, titanium alloy powder in this particle size range can obtain prints with excellent mechanical properties and biocompatibility through an optimized sintering process, meeting the strict standards of medical devices for material safety and reliability.

[0056] Specifically in this solution, in step 1, the diameter of the carbon nanotube is 20-30 nm and the length is 10-20 μm; the particle size of the nano-ceramic particles is preferably 30-40 nm; and the particle size of the nano-metal particles is preferably 20-30 nm.

[0057] In this embodiment: the diameter of the carbon nanotubes is 20-30nm, and the length is 10-20μm. Carbon nanotubes have a unique tubular structure and excellent mechanical and electrical properties. When mixed with metal matrix powder, carbon nanotubes of this size can be effectively embedded in the gaps between metal particles to form a good interface bond. The diameter is in the range of 20-30nm, which can not only ensure that the carbon nanotubes have sufficient strength and rigidity to strengthen the metal matrix, but also make it relatively easy to disperse during the mixing process. Carbon nanotubes with a length of 10-20μm can form a certain network structure in the metal matrix, further improving the conductivity of the material and the anisotropy of the mechanical properties. For example, when preparing 3D printed parts that need to have good conductive properties, carbon nanotubes of this size can significantly improve the conductivity of the material, while enhancing the overall strength of the material, making it suitable for 3D printing manufacturing in fields such as electronic equipment;

[0058] For nano-ceramic particles, the particle size is preferably 30-40nm. Nano-ceramic particles have the characteristics of high hardness, high wear resistance and high temperature resistance. In this embodiment, the particle size of 30-40nm enables it to be evenly dispersed in the metal matrix, avoiding local stress concentration or uneven performance caused by excessively large particles. When used to enhance 3D printed metal powder materials, nano-ceramic particles of this particle size can form a hard protective film on the surface of the material, improving the wear resistance and corrosion resistance of the material. For example, in the 3D printing of automotive engine parts, the use of metal powder materials containing nano-ceramic particles of this particle size can significantly improve the service life and working performance of parts, and resist harsh working conditions such as high temperature, high pressure and wear;

[0059] The particle size of the nano-metal particles is preferably 20-30nm. Nano-metal particles can improve the toughness and conductivity of the metal matrix and other properties. The particle size of 20-30nm allows the nano-metal particles to have a large specific surface area, which can fully contact and interact with the metal matrix. During the 3D printing process, the nano-metal particles can fill the tiny pores between the metal matrix particles and improve the density and uniformity of the material. For example, when preparing electronic packaging materials, using 3D printing metal powder materials containing nano-metal particles of this particle size can reduce the resistance of the material, improve the heat dissipation performance and packaging quality of electronic components, and enhance the mechanical properties of the material to ensure the reliability and stability of electronic equipment in complex working environments.

[0060] Specifically in this scheme, in step 2, when the metal matrix powder is stainless steel powder, the insulation temperature of the vacuum heating furnace is preferably 400°C, and the insulation time is 3 hours; when the metal matrix powder is aluminum alloy powder, the insulation temperature is preferably 350°C, and the insulation time is 2.5 hours; when the metal matrix powder is titanium alloy powder, the insulation temperature is preferably 450°C, and the insulation time is 3.5 hours.

[0061] In this embodiment: the insulation temperature of the vacuum heating furnace is preferably 400°C, and the insulation time is 3 hours. Under this temperature and time condition, the stainless steel powder can fully remove the adsorbed gas and moisture on the surface, and at the same time will not cause obvious changes in the crystal structure of the stainless steel, thereby ensuring the physical and chemical stability of the powder. The temperature of 400°C can volatilize impurities on the surface of the powder, improve the purity of the powder, and lay the foundation for subsequent good combination with nano-enhanced particles. The 3-hour insulation time can ensure that heat is evenly transferred to the inside of the powder, so that the entire powder system reaches a stable state. In actual operation, this parameter combination can be achieved through precise temperature control and time setting, improving the stability and repeatability of the production process, thereby ensuring that the prepared nano-enhanced stainless steel 3D printing metal powder material has good performance and quality consistency.

[0062] For aluminum alloy powder, the holding temperature is preferably 350°C and the holding time is 2.5 hours. Aluminum alloys have a relatively low melting point and high activity, so relatively low holding temperatures and shorter holding times are required. A temperature of 350°C can effectively remove adsorbents on the surface of aluminum alloy powders while avoiding excessive oxidation of aluminum alloys. A holding time of 2.5 hours can reduce energy consumption and production cycles while ensuring the treatment effect. Under this parameter, the aluminum alloy powder can maintain good performance, and in the subsequent mixing and processing process with nano-enhanced particles, it can better play its light weight and good thermal conductivity. Characteristics, to prepare high-performance nano-enhanced aluminum alloy 3D printing metal powder materials suitable for aerospace and other fields.

[0063] When the metal matrix powder is titanium alloy powder, the holding temperature is preferably 450°C and the holding time is 3.5 hours. Titanium alloy has high chemical activity and melting point, and requires a higher temperature to remove surface impurities and obtain a good surface state. The holding temperature of 450°C can decompose and volatilize impurities such as oxides on the surface of the titanium alloy powder, improve the activity and surface energy of the powder, and facilitate the combination with nano-enhanced particles. The 3.5-hour holding time can ensure that the temperature inside the titanium alloy powder is evenly distributed, achieving a stable treatment effect. In applications in the fields of medical devices and other fields, this parameter combination can prepare nano-enhanced titanium alloy 3D printing metal powder materials with excellent mechanical properties and biocompatibility, meeting the high-precision and high-performance requirements for medical devices such as implants.

[0064] Specifically in this scheme, in step 2, during the ultrasonic dispersion treatment, if the nano-reinforced particles are nano-carbon tubes, the mass fraction of the surfactant is preferably 2%, and the ultrasonic treatment time is 45 minutes; if the nano-reinforced particles are nano-ceramic particles, the mass fraction of the surfactant is preferably 1.5%, and the ultrasonic treatment time is 50 minutes; if the nano-reinforced particles are nano-metal particles, the mass fraction of the surfactant is preferably 2.5%, and the ultrasonic treatment time is 35 minutes.

[0065] In this embodiment: (a) For the ultrasonic dispersion treatment of carbon nanotubes, a surfactant mass fraction of 2% is used, and the ultrasonic treatment time is 45 minutes. Carbon nanotubes are prone to agglomeration due to their high aspect ratio and large surface energy. The 2% surfactant mass fraction can effectively reduce the surface tension between carbon nanotubes, so that they are better dispersed in the solution. After 45 minutes of ultrasonic treatment, the cavitation effect and mechanical stirring effect generated by ultrasonic vibration can fully break the agglomerates of carbon nanotubes, so that they are evenly dispersed in the solution. This dispersed state is conducive to the subsequent mixing with stainless steel powder, ensuring that the carbon nanotubes can be evenly attached to the surface of the stainless steel powder, thereby playing its reinforcing role in the 3D printing process and improving the strength and conductivity of the printed parts. For example, when preparing 3D printing materials for high-performance electronic device housings, the uniform dispersion of carbon nanotubes can make the printed parts have better electromagnetic shielding performance and mechanical strength.

[0066] (ii) Nano-ceramic particles: When the nano-reinforced particles are nano-ceramic particles, the mass fraction of the surfactant is preferably 1.5%, and the ultrasonic treatment time is 50 minutes. Nano-ceramic particles generally have high hardness and surface activity, and a surfactant content of 1.5% can make their surface better wetted and dispersed. The ultrasonic treatment time of 50 minutes can ensure that the nano-ceramic particles are fully dispersed in the solution and reduce the agglomeration phenomenon between the particles. When mixed with aluminum alloy powder, the evenly dispersed nano-ceramic particles can significantly improve the hardness, wear resistance and high temperature resistance of the aluminum alloy. For example, in the 3D printing of automotive engine parts, aluminum alloy materials reinforced with nano-ceramic particles can better resist high temperatures and wear, extending the service life of parts.

[0067] (iii) Nanometal particles: For nanometal particles, the mass fraction of the surfactant is preferably 2.5%, and the ultrasonic treatment time is 35 minutes. Nanometal particles are highly active and easily oxidized and agglomerated. 2.5% of surfactant can effectively prevent the oxidation of nanometal particles and promote their dispersion in the solution. 35 minutes of ultrasonic treatment can achieve uniform dispersion of nanometal particles in a shorter time, avoiding changes in particle properties that may be caused by excessive ultrasound. When mixed with titanium alloy powder, nanometal particles can improve the toughness and conductivity of titanium alloys. For example, in the 3D printing of titanium alloy implants in the field of medical devices, the addition of nanometal particles can make the implant have better biocompatibility and mechanical properties, and promote tissue growth and healing.

[0068] Specifically in this scheme, in step three, when the nano-reinforced particles are nano-carbon tube-reinforced stainless steel powder, the proportion of nano-carbon tubes to the mass of the stainless steel powder is preferably 1%, the stirring speed is 1500 rpm, and the stirring time is 3 hours; when the nano-reinforced particles are nano-alumina-reinforced aluminum alloy powder, the proportion of nano-alumina to the mass of the aluminum alloy powder is preferably 2%, the stirring speed is 1800 rpm, and the stirring time is 2.5 hours; when the nano-reinforced particles are nano-nickel-reinforced titanium alloy powder, the proportion of nano-nickel to the mass of the titanium alloy powder is preferably 1.5%, the stirring speed is 1600 rpm, and the stirring time is 3.5 hours.

[0069] In this embodiment: (a) Carbon nanotubes reinforced stainless steel powder: When the nano-reinforced particles are carbon nanotubes reinforced stainless steel powder, the proportion of carbon nanotubes to the mass of the stainless steel powder is preferably 1%, the stirring speed is 1500 rpm, and the stirring time is 3 hours. The 1% carbon nanotube content can effectively improve the performance of stainless steel without having too much impact on its processing performance. At a stirring speed of 1500 rpm, the carbon nanotubes and stainless steel powder can be fully mixed, and the stirring time of 3 hours can ensure the uniformity of the mixing. This uniform mixing allows the carbon nanotubes to form a good dispersion state in the stainless steel matrix. During the 3D printing process, it can significantly improve the strength and toughness of the printed parts while maintaining the corrosion resistance of the stainless steel. For example, when manufacturing high-strength mechanical parts, carbon nanotube-reinforced stainless steel 3D printing materials can meet the strict requirements of the parts for mechanical properties.

[0070] (ii) Nano-alumina reinforced aluminum alloy powder: For nano-alumina reinforced aluminum alloy powder, the proportion of nano-alumina to the mass of the aluminum alloy powder is preferably 2%, the stirring speed is 1800 rpm, and the stirring time is 2.5 hours. The 2% nano-alumina content can effectively improve the hardness and wear resistance of the aluminum alloy. The higher stirring speed of 1800 rpm enables the nano-alumina to be better dispersed in the aluminum alloy powder, and the 2.5-hour stirring time ensures the adequacy of the mixing. In applications in the aerospace field, this nano-enhanced aluminum alloy material can be used to manufacture lightweight and high-performance parts, such as aircraft structural parts, to improve aircraft performance and fuel efficiency.

[0071] (III) Nano-nickel reinforced titanium alloy powder: When the nano-reinforced particles are nano-nickel reinforced titanium alloy powder, the proportion of nano-nickel in the mass of the titanium alloy powder is preferably 1.5%, the stirring speed is 1600 rpm, and the stirring time is 3.5 hours. The 1.5% nano-nickel content can improve the toughness and conductivity of the titanium alloy to a certain extent. The stirring speed of 1600 rpm and the stirring time of 3.5 hours can make the nano-nickel evenly distributed in the titanium alloy powder, thereby improving the comprehensive performance of the material. In the field of medical devices, nano-nickel reinforced titanium alloy 3D printing materials can be used to manufacture implants with better biocompatibility and mechanical properties, such as artificial joints, etc., to improve the quality of life of patients.

[0072] Specifically in this scheme, in step four, when ball milling a mixed powder of stainless steel powder and nano-reinforced particles, the ball mill speed is preferably 400 rpm, the ball milling time is 10 hours, and the ball-to-material ratio is 8:1; when ball milling a mixed powder of aluminum alloy powder and nano-reinforced particles, the ball mill speed is preferably 350 rpm, the ball milling time is 11 hours, and the ball-to-material ratio is 7:1; when ball milling a mixed powder of titanium alloy powder and nano-reinforced particles, the ball mill speed is preferably 450 rpm, the ball milling time is 9 hours, and the ball-to-material ratio is 9:1.

[0073] In this embodiment: (a) Mixed powder of stainless steel powder and nano-reinforced particles: When the mixed powder of stainless steel powder and nano-reinforced particles is ball-milled, the ball mill speed is preferably 400 rpm, the ball milling time is 10 hours, and the ball-to-material ratio is 8:1. The speed of 400 rpm can effectively refine the powder particles and promote the uniform dispersion of the nano-reinforced particles in the stainless steel matrix while avoiding excessive wear of the powder. The 10-hour ball milling time can ensure the adequacy of the ball milling effect and enable the mixed powder to achieve a good microstructure. The 8:1 ball-to-material ratio can ensure sufficient contact and interaction between the grinding balls and the powder, thereby improving the ball milling efficiency. In actual production, this combination of ball milling parameters can produce nano-reinforced stainless steel 3D printing metal powder materials with excellent performance, which can be used to manufacture high-precision and high-performance industrial parts.

[0074] (ii) Mixed powder of aluminum alloy powder and nano-reinforced particles: For the mixed powder of aluminum alloy powder and nano-reinforced particles, the ball mill speed is preferably 350 rpm, the ball milling time is 11 hours, and the ball-to-material ratio is 7:1. Since the hardness of aluminum alloy is relatively low, the speed of 350 rpm can prevent excessive deformation and oxidation of aluminum alloy powder. The longer ball milling time of 11 hours can fully improve the microstructure of the powder and the dispersion state of the nano-reinforced particles. The ball-to-material ratio of 7:1 can reduce the wear on the equipment while ensuring the ball milling effect. In the 3D printing application in the aerospace field, the nano-reinforced aluminum alloy material prepared under this ball milling parameter can meet the requirements for lightweight and high performance of parts. (iii) Mixed powder of titanium alloy powder and nano-reinforced particles: When ball milling the mixed powder of titanium alloy powder and nano-reinforced particles, the ball mill speed is preferably 450 rpm, the ball milling time is 9 hours, and the ball-to-material ratio is 9:1. Titanium alloy has high hardness and strength, and requires a relatively high speed to achieve effective ball milling. The rotation speed of 450 rpm can fully mix and refine the titanium alloy powder and nano-reinforced particles. The 9-hour ball milling time can ensure the stability and consistency of the ball milling effect. The 9:1 ball-to-material ratio can provide sufficient energy input to promote the good combination of nano-reinforced particles and the titanium alloy matrix. In applications such as medical devices, the nano-reinforced titanium alloy material prepared under this ball milling parameter can meet the high performance requirements of products such as implants.

[0075] Specifically in this scheme, in step five, the drying temperature is preferably 100°C and the drying time is 6 hours; when screening stainless steel powder-based nano-enhanced materials, the powder with a particle size of 20-30μm is vibrated and screened; when screening aluminum alloy powder-based nano-enhanced materials, the powder with a particle size of 30-40μm is vibrated and screened; when screening titanium alloy powder-based nano-enhanced materials, the powder with a particle size of 15-45μm is vibrated and screened.

[0076] In this embodiment: the drying temperature is preferably 100°C and the drying time is 6 hours. The drying temperature of 100°C is relatively low, which can prevent oxidation or other chemical reactions of the powder during the drying process, and can effectively remove moisture from the powder. The 6-hour drying time can ensure that the powder is fully dried and reaches a suitable moisture content to meet the requirements of the subsequent 3D printing process. In actual production, this drying parameter can ensure the quality stability of nano-enhanced 3D printing metal powder materials and prevent printing defects or performance degradation caused by residual moisture.

[0077] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing nano-enhanced 3D printing metal powder material, characterized in that: The following steps are involved: Step 1: Raw material preparation: Select metal matrix powder, which is one of stainless steel powder, aluminum alloy powder or titanium alloy powder, and the powder particle size range is 10-50 μm; Prepare nano-reinforced particles, which are one of nano-carbon tubes, nano-ceramic particles (such as aluminum oxide, zirconium oxide, etc.) or nano-metal particles (such as nickel, cobalt, etc.), and the particle size of the nano-particles ranges from 10 to 50 nm. Step 2: Surface treatment: Place the metal matrix powder in a vacuum heating furnace and keep it at 300-500°C for 2-4 hours; The nano-enhanced particles are placed in a solution containing a surfactant for ultrasonic dispersion treatment, wherein the mass fraction of the surfactant is 1%-3%, and the ultrasonic treatment time is 30-60 minutes. Step 3: Mixing process: Add the surface treated metal matrix powder and nano-enhanced particle solution into a high-speed stirrer at a ratio of 0.5% to 3% of the mass of the nano-enhanced particles to the metal matrix powder, and stir at a speed of 1000 to 2000 rpm for 2 to 4 hours. Step 4: ball milling: put the mixed powder into a ball mill for ball milling. The speed of the ball mill is 300-500 rpm. The ball milling time is 8-12 hours. Stainless steel balls are used as grinding balls. The ball-to-material ratio is 5:1-10:

1. Step 5: Drying and sieving: The ball-milled powder is dried in a vacuum drying oven at a drying temperature of 80-120°C for 4-8 hours; The dried powder was sieved using a vibrating screen, and powder with a particle size range of 10-50 μm was selected as nano-enhanced 3D printing metal powder material.

2. A method for preparing a nano-enhanced 3D printing metal powder material according to claim 1, characterized in that: In step one, the particle size of the stainless steel powder is preferably 20-30 μm, the particle size of the aluminum alloy powder is preferably 30-40 μm, and the particle size of the titanium alloy powder is preferably 15-45 μm.

3. The method for preparing a nano-enhanced 3D printing metal powder material according to claim 1, characterized in that: In step 1, the diameter of the carbon nanotubes is 20-30 nm and the length is 10-20 μm; the particle size of the nano-ceramic particles is preferably 30-40 nm; and the particle size of the nano-metal particles is preferably 20-30 nm.

4. The method for preparing a nano-enhanced 3D printing metal powder material according to claim 1, characterized in that: In step 2, when the metal matrix powder is stainless steel powder, the insulation temperature of the vacuum heating furnace is preferably 400°C, and the insulation time is 3 hours; when the metal matrix powder is aluminum alloy powder, the insulation temperature is preferably 350°C, and the insulation time is 2.5 hours; when the metal matrix powder is titanium alloy powder, the insulation temperature is preferably 450°C, and the insulation time is 3.5 hours.

5. The method for preparing a nano-enhanced 3D printing metal powder material according to claim 1, characterized in that: In step 2, during the ultrasonic dispersion treatment, if the nano-reinforced particles are nano-carbon tubes, the mass fraction of the surfactant is preferably 2%, and the ultrasonic treatment time is 45 minutes; if the nano-reinforced particles are nano-ceramic particles, the mass fraction of the surfactant is preferably 1.5%, and the ultrasonic treatment time is 50 minutes; if the nano-reinforced particles are nano-metal particles, the mass fraction of the surfactant is preferably 2.5%, and the ultrasonic treatment time is 35 minutes.

6. The method for preparing a nano-enhanced 3D printing metal powder material according to claim 1, characterized in that: In step three, when the nano-reinforced particles are nano-carbon tube-reinforced stainless steel powder, the proportion of nano-carbon tubes to the mass of the stainless steel powder is preferably 1%, the stirring speed is 1500 rpm, and the stirring time is 3 hours; when the nano-reinforced particles are nano-alumina-reinforced aluminum alloy powder, the proportion of nano-alumina to the mass of the aluminum alloy powder is preferably 2%, the stirring speed is 1800 rpm, and the stirring time is 2.5 hours; when the nano-reinforced particles are nano-nickel-reinforced titanium alloy powder, the proportion of nano-nickel to the mass of the titanium alloy powder is preferably 1.5%, the stirring speed is 1600 rpm, and the stirring time is 3.5 hours.

7. The method for preparing a nano-enhanced 3D printing metal powder material according to claim 1, characterized in that: In step four, when ball milling a mixed powder of stainless steel powder and nano-reinforced particles, the ball mill speed is preferably 400 rpm, the ball milling time is 10 hours, and the ball-to-material ratio is 8:1; when ball milling a mixed powder of aluminum alloy powder and nano-reinforced particles, the ball mill speed is preferably 350 rpm, the ball milling time is 11 hours, and the ball-to-material ratio is 7:1; when ball milling a mixed powder of titanium alloy powder and nano-reinforced particles, the ball mill speed is preferably 450 rpm, the ball milling time is 9 hours, and the ball-to-material ratio is 9:

1.

8. The method for preparing a nano-enhanced 3D printing metal powder material according to claim 1, characterized in that: In step five, the drying temperature is preferably 100°C and the drying time is 6 hours; when screening stainless steel powder-based nano-enhanced materials, the powder with a particle size of 20-30μm is vibrated and screened; when screening aluminum alloy powder-based nano-enhanced materials, the powder with a particle size of 30-40μm is vibrated and screened; when screening titanium alloy powder-based nano-enhanced materials, the powder with a particle size of 15-45μm is vibrated and screened.